Aetiology of pleural effusions diagnosed by routine culture and molecular techniques in children living in a high tuberculosis-endemic setting - Wordui, Seyram (Department of Paediatrics and Child Health, 2025)
BACKGROUND: Confirming aetiology of pleural effusion in children may be difficult in tuberculosis (TB)-endemic settings. We investigated the role of polymerase chain reaction (PCR) and routine biochemical tests in discriminating pleural effusion caused by bacteria from other aetiologies. METHODS: This is a post-hoc analysis of a cross-sectional study among children with pleural effusion in a tertiary hospital in South Africa, incorporating data from PCR testing of stored pleural fluid. Aetiological classification was defined by microbiological confirmation. RESULTS: Ninety-one children were enrolled, median age 31 months (IQR 12-102). Aetiology of pleural effusion was 40 % (n=36/91) bacteria, 11% (n=10/91) TB, 3% (n=3/91) viruses, 11% (n=10/91) polymicrobial and 35% (n=32/91) had no pathogen identified. The commonest pathogen was Staphylococcus aureus (n=27/91; 30%) with similar yields on culture and PCR, followed by Streptococcus pneumoniae (n=12/91; 13%), detected more commonly by PCR. PCR reduced the number of children with unconfirmed aetiologies from 48 to 32. Characteristics of children with no pathogen most resembled those with TB. Pleural fluid lactate dehydrogenase ≥1716 U/L best discriminated bacterial pleural effusion from other aetiologies (sensitivity of 86%; specificity 95%). CONCLUSION: PCR improved detection of pathogens and reduced number of children with unconfirmed aetiologies in presumed exudative pleural effusion.